Plasma and tissue clindamycin antimicrobial activity after parenteral administration to cats under surgical conditions - Passini, Sabrina Mariela (2017)
Clindamycin plasma and tissue disposition in cats under surgical conditions after a single intravenous (IV), intramuscular (IM) and subcutaneous (SC) administration at a dose rate of 10 mg/kg were studied. After intravenous, intramuscular and subcutaneous administration, peak plasma concentrations were 10.93±3.78 μg/mL (Cp(0)), 5.93±1.18 μg/mL (Cmax)) and 6.30±0.88 μg/mL (Cmax)), respectively. Eight hours after clindamycin IV, IM and SC administration plasma concentrations declined to 2.01±0.61 μg/mL, 2.96±0.43 μg/mL and 3.36±0.97 μg/mL, respectively. Sixty to 90 minutes after clindamycin administration, tissue concentrations ranged from a minimum in subcutaneous tissue of 4.90 μg/g (IV), 3.06 μg/g (IM) and, 3.13 μg/g (SC) to a maximum in uterus of 13.41 μg/g (IV), 14.07 μg/g (IM) and, 14.44 μg/g (SC). The lowest tissue/plasma concentration ratio for the three administration routes was observed in subcutaneous tissue, while the highest was observed at genital level (ovary for IV and IM and uterus for SC). Estimated efficacy predictor (AUC/MIC), considering MIC breakpoint for bacteria isolated from animals, indicates that clindamycin administered IV, IM or SC at the studied dose is appropriated for perioperative prophylactic protocols and that given with a dose interval of 12 hours would be effective for susceptible infection treatment in cats.